Mechanical and thermal properties of epoxy/tamarind shell composite - Ku Zarina Ku Ahmad,; Abbas Harun,; Mohd Khairul Faidzi,; Raja Nor Othman,; A. A Kamarolzaman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study explores the potential of tamarind shells as a filler in epoxy composites. The tamarind shells were collected from local supply and processed by washing it repeatedly using distilled water. The tamarind shells were dried and crushed to form fine particles. Epoxy composites were produced by mixing epoxy and hardener with varying (25,40,50,60) wt % of tamarind shells powder to achieve the desired properties. The samples underwent density test, flexural test, hardness test, thermal stability test, and morphology in order to analyse the mechanical and thermal properties of the samples. With the addition of tamarind shell particle, hardness and flexural strength show improvement about ~ 80% and 147%, respectively. However, density and thermal stability show decrement in value.